Studi Perbandingan Kepuasan Konsumen Berbasis Online dan Belanja Offline terhadap Loyalitas Konsumen - Irene Vikining Astuty; I Komang Winatha; Rahmah Dianti Putri (FKIP Universitas Lampung, 2020)
This study aims to compare online-based shopping consumer satisfaction using social media Instagram and direct shopping (offline) to consumer loyalty in Bandar Lampung Melstore Shop. The method used in this research is an experiment using a comparative and survey approach. This study's sample is the Bandar Lampung Melstore Shop consumers who shop online and offline totaling 96 respondents. The technique used is nonprobability sampling with the type of purposive sampling. The data collection uses observation and questionnaires. Data collected through a questionnaire is then processed using the SPSS 15.0 program. The results obtained by using the SPSS 15.0 program indicate that the variable of customer satisfaction when shopping online and offline has a significant difference. It has an impact on consumer loyalty, both online and offline.